2009
DOI: 10.1080/10669860903133468
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Realities and Constraints on Change: The Case of SME in Russia

Abstract: This article presents the results of exploratory field research investigating the impact of the enabling institutional environment and internal firm capabilities in the information technology sector in St. Petersburg, Russia. Through a series of semi-structured interviews and confirmatory research through the UNDP and UNIDO, the study finds the emerging institutional environment remains weak, unpredictable and unstable, creating challenges for SMEs to contribute to the growth and development of the Russian eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 27 publications
(31 reference statements)
2
21
0
Order By: Relevance
“…Batjargal, 2007a). A qualitative approach was taken in only 4 papers (Bruton and Rubanik, 1997;Kapustkina et al, 2008;Molz et al 2009;Rogers, 2006). The reasons for selecting a particular analytical approach were poorly reported in most of the studies.…”
Section: Analytical Approaches and Types Of Research In The Studies Rmentioning
confidence: 99%
“…Batjargal, 2007a). A qualitative approach was taken in only 4 papers (Bruton and Rubanik, 1997;Kapustkina et al, 2008;Molz et al 2009;Rogers, 2006). The reasons for selecting a particular analytical approach were poorly reported in most of the studies.…”
Section: Analytical Approaches and Types Of Research In The Studies Rmentioning
confidence: 99%
“…The aforementioned determinants, both demand and supply side, are relevant for all countries, however, in transitioning economies, their impact on growth and sometimes the vector of a business's development is determined by the features of the institutional environment. The body of empirical research on SME performance in developing economies found a robust relationship between firm performance and the quality of institutions [Aidis et al, 2008;Molz et al, 2009;Blagojevic, Damijan, 2013;Sharafutdinova, Kisunko, 2014;Yukhanaev et al, 2015;Volchek et al, 2013a,b;Wang, You, 2012;Krasniki, Desai, 2016;Welter, Smallbone, 2011]. However, the mechanism behind their interactions remains poorly studied.…”
Section: Determinants and Patterns Of Sme Growth: The Russian Contextmentioning
confidence: 99%
“…The determinants of firm growth described above, such as supply-and demand-side factors, are still valid for firms operating within emerging economies. However, their effectiveness and the direction of their effect is often determined by the idiosyncrasies of the institutional environment [Marcelin, Mathur, 2015;Cuaresma et al, 2013;Volchek et al, 2013a,b;Molz et al, 2009;Dallago, 2000;Blagojevic, Damijan, 2013;Welter, Smallbone, 2011;Yukhanaev et al, 2015].…”
Section: Determinants and Patterns Of Sme Growth: The Russian Contextmentioning
confidence: 99%
“…The aforementioned determinants, both demand and supply side, are relevant for all countries, however, in transitioning economies, their impact on growth and sometimes the vector of a business's development is determined by the features of the institutional environment. The body of empirical research on SME performance in developing economies found a robust relationship between firm performance and the quality of institutions Molz et al, 2009;Blagojevic, Damijan, 2013;Sharafutdinova, Kisunko, 2014;Yukhanaev et al, 2015;Volchek et al, 2013a,b;Wang, You, 2012;Krasniki, Desai, 2016;. However, the mechanism behind their interactions remains poorly studied.…”
Section: Determinants and Patterns Of Sme Growth: The Russian Contextmentioning
confidence: 99%
“…The determinants of firm growth described above, such as supply-and demand-side factors, are still valid for firms operating within emerging economies. However, their effectiveness and the direction of their effect is often determined by the idiosyncrasies of the institutional environment [Marcelin, Mathur, 2015;Cuaresma et al, 2013;Volchek et al, 2013a,b;Molz et al, 2009;Dallago, 2000;Blagojevic, Damijan, 2013;Yukhanaev et al, 2015].…”
Section: Determinants and Patterns Of Sme Growth: The Russian Contextmentioning
confidence: 99%